2003
DOI: 10.1108/00346650310488516
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes to service quality – the expectation gap

Abstract: In the competitive environment in which hospitality businesses exist, the quality of service is a vital mechanism used to achieve a competitive advantage. Quality is a difficult construct to quantify however the ability to measure quality is key to assessing whether or not the industry provides the service consumers desire. Consumers hold the key to business survival and success. The aim of this study was to investigate how closely consumer expectations of service, and manager and staff perceptions of consumer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
59
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(64 citation statements)
references
References 14 publications
2
59
0
3
Order By: Relevance
“…This may be because of their expectations having been met to a large extent in this dimension. Our finding in this section is parallel to a number of works [24,25,28] whereas is not consistent with some other studies [9,[18][19][20]. As a part of effective provision of quality services it is necessary to be aware of customer expectations.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…This may be because of their expectations having been met to a large extent in this dimension. Our finding in this section is parallel to a number of works [24,25,28] whereas is not consistent with some other studies [9,[18][19][20]. As a part of effective provision of quality services it is necessary to be aware of customer expectations.…”
Section: Discussionsupporting
confidence: 78%
“…As a part of effective provision of quality services it is necessary to be aware of customer expectations. This is also essential for survival in a competitive environment [9]. In general, women's expectations were not met in the health centers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At that time, manifested centrifugal relation among quality of customer services, performance improvement and organizational competitiveness have been studied. This relation clearly showed that the improvement of customer services will lead in its turn to an improvement in the performance and competitiveness (Douglas & Connor, 2003;Rosen, Karwan, & Scribner, 2003). Certain standards and indicators of customer satisfaction and service quality are used by service units' administrators to value customers' needs by the institution.…”
Section: Introductionmentioning
confidence: 99%
“…The present study assumes service quality perception as desires and needs of customers as it will allow discovering exactly what service providers should offer based on customer past experience and interaction (Douglas and Connor, 2003). Negi, (2009) suggested that, it is mandatory for organizations to understand, measure and evaluate customer's perceptions and expectations for the identification of significant gaps in service delivery to ensure customer satisfaction.…”
Section: Customer Perceptionmentioning
confidence: 99%